Dark aerobic sulfide oxidation by anoxygenic phototrophs in anoxic waters. (4th March 2019) - Berg, Jasmine S.; Pjevac, Petra; Sommer, Tobias; Buckner, Caroline R.T.; Philippi, Miriam; Hach, Philipp F.; Liebeke, Manuel; Holtappels, Moritz; Danza, Francesco; Tonolla, Mauro; Sengupta, Anupam; Schubert, Carsten J.; et al.
Summary: Anoxygenic phototrophic sulfide oxidation by green and purple sulfur bacteria (PSB) plays a key role in sulfide removal from anoxic shallow sediments and stratified waters. Although some PSB can also oxidize sulfide with nitrate and oxygen, little is known about the prevalence of this chemolithotrophic lifestyle in the environment. In this study, we investigated the role of these phototrophs in light‐independent sulfide removal in the chemocline of Lake Cadagno. Our temporally resolved, high‐resolution chemical profiles indicated that dark sulfide oxidation was coupled to high oxygen consumption rates of 9 μM O2 ·h −1 . Single‐cell analyses of lake water incubated with 13 CO2 in the dark revealed that Chromatium okenii was to a large extent responsible for aerobic sulfide oxidation and it accounted for up to 40% of total dark carbon fixation. The genome of Chr. okenii reconstructed from the Lake Cadagno metagenome confirms its capacity for microaerophilic growth and provides further insights into its metabolic capabilities. Moreover, our genomic and single‐cell data indicated that other PSB grow microaerobically in these apparently anoxic waters. Altogether, our observations suggest that aerobic respiration may not only play an underappreciated role in anoxic environments but also that organisms typically considered strict anaerobes may be involved.